EKSISTENSI BAHASA INDONESIA PADA MASA PANDEMI - Rina Devianty (Universitas Islam Negeri Sumatera Utara, 2020)
Indonesian serves as a unifying language in Indonesia among the various ethnic groups in the archipelago. However, in reality the function of language as a unifier is still just a camouflage because in fact Indonesian speakers still prefer foreign languages more than Indonesian. This can be considered, both in print and electronic media. The widespread use of foreign languages during the Covid-19 pandemic made Indonesian as if it did not have a function as a unifying language. This article explains the large number of uses of foreign vocabulary when delivering information related to the Covid-19 pandemic news. All foreign vocabulary related to the Covid-19 pandemic outbreak will actually be easily understood by all levels of Indonesian society if they use Indonesian. Understanding the language spoken by government officials regarding the handling of the Covid-19 pandemic will probably make the public more aware of the importance of maintaining health so that they can avoid the Covid-19 virus.Key words: Existence, Indonesian Language, Pandemic